PENERAPAN LAYANAN PRIVATE CLOUD COMPUTING PADA LABORATORIUM KOMPUTER UNIVERSITAS BINA DARMA PALEMBANG - Maria Ulfa; Helda Yudiastuti (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
The computer lab is one of the media facilities for learning and research at the University of Bina Darma Palembang, where the performance of the computer labs greatly affect the quality possessed by a laboratory computer, to maintain the performance of a computer lab needed a strategy to continue to enhance the development of the computer lab. Utilization of cloud computing for data storage, application software together as well as the use of infrastructure and hardware on a computer network. The design of cloud computing for computer laboratorium Universitas Bina Darma Palembang aimed at a preliminary design for a computer lab development as a center of learning and research for faculty and students. The design uses a cloud computing service model of Software as a Service (SaaS) and using the model of private cloud computing.